Relawan Pajak Ikuti Kegiatan Asistensi Pajak bagi Tenaga Pendidik dan Karyawan UNY melalui Roadshow Pajak dan Tax Clinic - Meita Dwi Cahyani; Dian Juliani (Jurnal Pelayanan Masyarakat, 2024)
UNY Tax Volunteer service activity aims to accompany teaching staff and employees in reporting tax returns and as a forum for improving effective communication skills for students. Apart from that, SPT reporting assistance activities are also needed to help UNY teaching staff and employees who have difficulty or do not understand the reporting process. This tax assistance activity involves students who register as Tax Volunteers. Activities carried out by UNY Tax Volunteers include material provision, Tax Roadshow, and Tax Clinic. With the presence of Tax Volunteers, teaching staff and employees feel helped in reporting SPT. The results of the UNY Tax Volunteer program show an increase in effective communication skills in students. This activity is not only beneficial for students, but has also been proven to help UNY teaching staff and employees in all faculties at UNY to be able to report tax returns on time and in accordance with applicable regulations.